The role of customer satisfaction in mediating the influence of customer experience and product quality on repurchase intentionThe Role of Customer Satisfaction in Mediating the Influence of Customer Experience and Product Quality on Repurchase Intention - Danardono, Benedikta Sekar Lintang Gemelia; Nuvriasari, Audita (Formosa Journal of Science and Technology, 2024)
The aim of this research is to analyze the influence of customer experience and product quality on repurchase intention with customer satisfaction as a mediator in the purchase of fashion products at Rubylicious Yogyakarta. The study was conducted by distributing questionnaires to Rubylicious Yogyakarta customers, using a quantitative approach to examine causal relationships. Data were collected through a Likert scale questionnaire from 100 respondents. The data analysis techniques used included descriptive analysis, inferential analysis, path analysis, and partial least squares. The results of the study indicate that customer experience and product quality do not have a significant effect on repurchase intention.  However, both have a positive and significant effect on customer satisfaction, which in turn has a positive and significant effect on repurchase intention. Customer satisfaction also significantly mediates the influence of customer experience and product quality on repurchase intention.